Análise da relação entre alterações bucais e manifestação cutânea de pacientes psoriáticos - Furtado, Lair Mambrini (2008)
Psoriasis is a chronic dermatologic disease that comets at least 3% of the world population. In the tropical countries, such as Brazil, it is considered an important factor of social exclusion. The clinic manifestation presents mainly papules and white plaque that are easily removed leaving at its place many small bleeding points known as Austpits sign. The disease may shows different clinic pattern and it can be find in different stage described as evaluative or acute and stable or asymptomatic. Oral manifestation is still a controversy in the literature. It has been described by some authors in clinical case reports as white or erythematous lesions, ulcers and descamative papules. Some of these reports tend to establish a direct relationship between the dermatologic manifestation and geographic and fissured tongues and others could not find the same occurrence. In the present study all the patients attended to the psoriasis ambulatory of the Uberlândia Federal University medical school passed into an oral exam in a period of 12 months. 36 patients were included in this study because they had been examined two times or more in a period bigger than three weeks, allowing establishing a relationship between the disease clinical stage and the oral manifestation. The oral lesions found in this study were two white plaques in the jugal mucosa, seven erythematous areas in the hard palate and two angular queilites, six fissured and one one association of geographic and fissured tongue. After all, it was not possible to make any specific association between dermatologic and oral manifestation because some oral lesions were present in both stage of psoriasis and otherwise, some were present in a stable stage and disappeared in the progressive. Also the incidence of the oral lesion identified in this study was similar to that found in a normal population.